Blue Rubber Bleb Nevus Syndrome in a Pakistani Child: a case report and regional literature review - Habib Qaiser; Kamran Sadiq; Bushra Afroze (Journal of the Pakistan Medical Association, 2022)
Blue rubber bleb nevus syndrome (BRBNS) is a rare disorder in which there is development of multiple venous malformations and haemangiomas in the skin and visceral organs. The lesions mostly involve the skin and gastrointestinal systems but other organs, including the liver, muscles, and the central nervous system, can also be involved. If untreated, affected individuals develop severe anaemia. Most cases are managed with iron supplementation and blood transfusions but some may require surgical resection, endoscopic sclerosis and laser photocoagulation. Here, we present a case of BRBNS in a four-year-old girl with multiple cutaneous lesions, melena and severe anaemia. Review of South Asian literature showed that only two cases (besides ours) have been reported from Pakistan and the rest were from India. This highlights the lack of awareness of BRBNS among physicians in Pakistan and the rest of South Asian countries. Keywords: Blue Rubber Bleb Nevus Syndrome, Child, Pakistan. Continuous...